Accelerated filtration of ultrasound images - Pupchenko, D.; Gorokhovatskyi, V. (Publishing House «Caravela», 2024)
The aim of this work is to create a high-speed algorithm for filtering ultrasound images that has the added property of edge preservation. The performance of popular methods is reviewed. A method of enhancing the existing method based on the decomposition of calculations into a one-dimensional space is proposed. The proposed solution significantly reduces computational costs without losing the efficacy of noise filtering. The overall effectiveness of ultrasound image filtering in terms of performance and quality has been experimentally confirmed.
Keywords: ultrasound images; filtering; speckle noise